Coma súbito como forma de presentación de la Endocarditis infecciosa - Pedro Magalhães; Raquel Torres; Rafaela Veríssimo (Sociedade Galega de Medicina Interna, 2024)
This case reports an uncommon presentation of Infectious endocarditis following a late hip periprosthetic infection. Patient presented with sudden coma with no abnormal head CT images. Nonconvulsive status epilepticus and central nervous system infection were excluded as well as significant metabolic, electrolyte or hormonal causes of neurological disfunction. Brain MRI revealed multiple recent small ischemic lesions suggestive of an embolic source. Serial blood cultures, under antibiotics, were negative but transoesophageal echocardiogram revealed a tricuspid valve vegetation along with a thin and mobile atrial septum where patency of the oval foramen could not be ruled out. A diagnosis of infectious endocarditis was established. A sudden coma with no CT changes is, to the best of the authors' knowledge and experience, a rare and previously undescribed presentation. This raises awareness that the diagnosis of brain septic emboli should be considered in the presence of sudden coma without other apparent causes.